A polyamide material with anti-oxidation and aging properties for automobile door frame trim

By mixing the polyamide resin, antioxidant H3386 and silicon -containing polyester and injection molding, the existing polyamide materials have poor effects on flame retardant, antioxidant and anti -aging, and achieve high performance The car door frame is made of polyamide.

CN118772624BActive Publication Date: 2025-01-28NANJING YUEBEIST NEW MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411017778.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-01-28
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

Existing polyamide materials are not effective in flame retardant, anti-oxidation and anti-aging, and are difficult to meet the high-performance needs of automotive door frame trims.

Method used

By mixed with polyamide resin, antioxidant H3386 and silicon -containing polyester, mix and mix together in a dual screw extrusion machine, and form a injection molding machine to prepare excellent flame retardant, stretching, antioxidant and anti -aging Effect polyamide material.

Benefits of technology

The high flame retardability, good stretching performance, and significant antioxidant and anti -aging effects of polyamide materials meet the high performance requirements of the car door frame trim.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004966251240000111
    Figure BDA0004966251240000111
  • Figure BDA0004966251240000112
    Figure BDA0004966251240000112
  • Figure BDA0004966251240000121
    Figure BDA0004966251240000121
Patent Text Reader

Abstract

The invention relates to the technical field of polyamide materials, and discloses an anti-oxidation and aging polyamide material for automobile door frame trim strips. The invention provides the anti-oxidation and aging polyamide material for automobile door frame trim strips by adding polyamide resin, antioxidant H3386 and silicon-containing hyperbranched polyester into a twin-screw extruder for melt blending, extrusion and granulation, and then injection molding by an injection molding machine. The sulfur element and silicon element contained in the silicon-containing hyperbranched polyester have good flame retardant effect; the silicon element also has good anti-oxidation and anti-aging effects; the silicon-containing hyperbranched polyester contains a large number of amide groups and has good compatibility with polyamide, and the hyperbranched structure further enhances the tensile properties of the polyamide material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyamide materials, in particular to an anti-oxidation and aging polyamide material for automobile door frame trim strips. Background Art

[0002] Polyamide has good wear resistance, mechanical properties, high temperature resistance and chemical resistance. It is the largest-produced general-purpose engineering plastic and is widely used in automotive decorative accessories, furniture and other fields. For example, patent CN117511188B discloses a high-flexibility polyamide material and its preparation method and injection molding process, which has high strength and low-temperature flexibility, but its flame retardant effect, antioxidant and anti-aging effect are not improved.

[0003] For example, the document "Preparation of Hyperbranched Polyester and Its Application in Plastic Processing" reports that a new type of carboxyl-terminated hyperbranched polyester is used to modify nylon-6 / glass fiber composite materials, thereby increasing the interface interaction and compatibility of the composite materials and improving the tensile strength and other properties of the composite materials. The present invention blends silicon-containing hyperbranched polyester with polyamide resin to improve its tensile strength. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies in the prior art, the present invention provides an anti-oxidation and anti-aging polyamide material for automobile door frame trims, which has good flame retardant, tensile, anti-oxidation and anti-aging effects.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention provides the following technical solution: an anti-oxidation and anti-aging polyamide material for automobile door frame trim, comprising the following weight components: 50-70 parts by weight of polyamide resin, 1-2 parts by weight of antioxidant H3386, and 5-8 parts by weight of silicon-containing hyperbranched polyester.

[0008] Preferably, the method for preparing the silicon-containing hyperbranched polyester comprises the following steps:

[0009] (1) adding maleic acid, thioglycolic acid and resin D301-R catalyst into a reactor filled with deionized water, stirring evenly, and reflux reacting at 85-95° C. for 3-6 hours. After the reaction is completed, filtering out the catalyst while hot, evaporating the deionized water at 80-95° C., drying and cooling to obtain carboxymethyl thiosuccinic acid;

[0010] (2) adding aminoethylaminopropylsilsesquioxane and acryloyl chloride to N,N-dimethylformamide solvent, stirring evenly, and then adding triethylamine catalyst thereto, reacting at 80-90° C. for 4-7 hours, and then performing reduced pressure distillation after the reaction, filtering and drying to obtain olefinated siloxane;

[0011] (3) adding divinyl glycol to N,N-dimethylformamide solvent, stirring and dispersing, then adding allyl mercaptan and benzoin dimethyl ether photoinitiator, irradiating with 365 nm ultraviolet light at 20-45° C. for 3-5 h, centrifuging, washing and drying to obtain intermediate 1;

[0012] (4) adding 5-10 parts by weight of intermediate 1, 6-9 parts by weight of olefinic siloxane, 4-8 parts by weight of divinyl glycol, and 5-12 parts by weight of olefinic phenolic resin to N,N-dimethylformamide solvent for dissolution, adding 0.5-1 parts by weight of azobisisobutyronitrile initiator after dissolution, reacting at 60-70° C. for 2-5 hours, removing the solvent by distillation under reduced pressure after the reaction, filtering, washing and drying to obtain intermediate 2;

[0013] (5) Dissolve carboxymethyl thiosuccinic acid and intermediate 2 in dimethyl sulfoxide solvent, then add 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, and reflux at 125-165° C. for 30-35 hours. After the reaction, cool and add methanol for precipitation, filter the solvent, wash with distilled water, acetone, and ethanol in turn to obtain a silicon-containing hyperbranched polyester.

[0014] Preferably, the mass ratio of maleic acid, thioglycolic acid and resin D301-R catalyst in (1) is 1.1-1.3:1:0.02-0.04.

[0015] Preferably, the mass ratio of aminoethylaminopropylsilsesquioxane, acryloyl chloride and triethylamine catalyst in (2) is 1.3-1.5:1:0.01-0.02.

[0016] Preferably, the mass ratio of divinyl glycol, allyl mercaptan and benzoin dimethyl ether photoinitiator in (3) is 1:0.8-1.3:0.02-0.05.

[0017] Preferably, the preparation method of the olefinic phenolic resin in (4) is:

[0018] S1. 10-16 parts by weight of a phenolic resin and 8-13 parts by weight of epichlorohydrin are mixed uniformly, reacted at 70-80 ° C for 6-12h, and then concentrated under reduced pressure and washed to obtain an epoxidized phenolic resin;

[0019] S2. Add 5-10 parts by weight of epoxidized phenolic resin and 10-16 parts by weight of acrylic acid to N,N-dimethylformamide solvent, stir and mix, react at 80-105°C for 10-18h, and then distill under reduced pressure, filter, wash and dry to obtain olefinated phenolic resin.

[0020] Preferably, the mass ratio of carboxymethyl thiosuccinic acid, the intermediate 2,4-dimethylaminopyridine, and N,N-dicyclohexylcarbodiimide in (5) is 1:0.8-1.2:0.01-0.03:0.02-0.05.

[0021] Preferably, the preparation method of the anti-oxidation and aging polyamide material for automobile door frame trims is: adding polyamide resin, antioxidant H3386, and silicon-containing hyperbranched polyester into a twin-screw extruder for melt blending, extrusion and granulation, the blending temperature is 210-245°C, and the extrusion temperature is 210-220°C; then injection molding by an injection molding machine, the injection molding temperature is 220-240°C, to obtain the anti-oxidation and aging polyamide material for automobile door frame trims.

[0022] (III) Beneficial technical effects

[0023] The invention adds polyamide resin, antioxidant H3386 and silicon-containing hyperbranched polyester into a twin-screw extruder for melt blending, extrusion and granulation, and then performs injection molding by an injection molding machine to obtain an anti-oxidation and aging polyamide material for automobile door frame trim strips.

[0024] The sulfur and silicon elements contained in the silicon-containing hyperbranched polyester have good flame retardant effects. The silicon element contained therein can form a dense and stable silicon-containing carbonized carbon protective layer on the surface of the substrate when burning, cut off the oxygen supply, and prevent the escape of volatiles from thermal degradation of the substrate, thereby achieving the purpose of flame retardancy; the sulfur element contained therein can accelerate the carbonization effect of the material when burning, and promote the formation of a dense carbon layer on the surface of the material. The phenolic resin therein also has a good flame retardant effect. The three complement each other and have a synergistic flame retardant effect; the silicon element therein also has good antioxidant and anti-aging effects; the silicon-containing hyperbranched polyester contains a large number of amide groups and has good compatibility with polyamide, and the hyperbranched structure further enhances the tensile properties of the polyamide material. DETAILED DESCRIPTION

[0025] Example 1

[0026] (1) adding maleic acid, thioglycolic acid, and resin D301-R catalyst into a reactor filled with deionized water, wherein the mass ratio of maleic acid, thioglycolic acid, and resin D301-R catalyst is 1.1:1:0.02, stirring evenly, and reflux reaction at 85° C. for 3 h. After the reaction is completed, the catalyst is filtered out while hot, and the deionized water is evaporated at 80° C., dried, and cooled to obtain carboxymethyl thiosuccinic acid;

[0027] (2) adding aminoethylaminopropyl silsesquioxane and acryloyl chloride to N,N-dimethylformamide solvent, stirring evenly, and then continuing to add triethylamine catalyst, wherein the mass ratio of aminoethylaminopropyl silsesquioxane, acryloyl chloride, and triethylamine catalyst is 1.3:1:0.01, reacting at 80° C. for 4 hours, and then distilling under reduced pressure after the reaction, filtering and drying to obtain olefinated siloxane;

[0028] (3) adding divinyl glycol to N,N-dimethylformamide solvent, stirring and dispersing, and then adding allyl mercaptan and benzoin dimethyl ether photoinitiator, wherein the mass ratio of divinyl glycol, allyl mercaptan and benzoin dimethyl ether photoinitiator is 1:0.8:0.02, irradiating with 365 nm ultraviolet light at 20° C. for 3 h, centrifuging after the end, washing and drying to obtain intermediate 1;

[0029] (4) 10 parts by weight of phenolic resin and 8 parts by weight of epichlorohydrin are mixed uniformly, reacted at 70° C. for 6 hours, and then concentrated under reduced pressure and washed to obtain an epoxidized phenolic resin;

[0030] (5) adding 5 parts by weight of epoxidized phenolic resin and 10 parts by weight of acrylic acid to N,N-dimethylformamide solvent, stirring and mixing, reacting at 80° C. for 10 hours, and then distilling under reduced pressure, filtering, washing and drying to obtain an olefinated phenolic resin;

[0031] (6) adding 5 parts by weight of intermediate 1, 6 parts by weight of olefinic siloxane, 4 parts by weight of divinyl glycol, and 5 parts by weight of olefinic phenolic resin to N,N-dimethylformamide solvent for dissolution, adding 0.5 parts by weight of azobisisobutyronitrile initiator after dissolution, reacting at 60° C. for 2 h, and removing the solvent by distillation under reduced pressure after the reaction, filtering, washing and drying to obtain intermediate 2;

[0032] (7) dissolving carboxymethyl thiosuccinic acid and intermediate 2 in a dimethyl sulfoxide solvent, then adding 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, wherein the mass ratio of carboxymethyl thiosuccinic acid, intermediate 2, 4-dimethylaminopyridine, and N,N-dicyclohexylcarbodiimide is 1:0.8:0.01:0.02, and reflux at 125° C. for 30 hours. After the reaction, cool and add methanol for precipitation, filter the solvent, and wash with distilled water, acetone, and ethanol in turn to obtain a silicon-containing hyperbranched polyester;

[0033] (8) 50 parts by weight of polyamide resin, 1 part by weight of antioxidant H3386, and 5 parts by weight of silicon-containing hyperbranched polyester are added to a twin-screw extruder for melt blending, extrusion and granulation. The blending temperature is 210° C. and the extrusion temperature is 210° C.; then, the mixture is injection molded by an injection molding machine at an injection molding temperature of 220° C. to obtain an anti-oxidative and anti-aging polyamide material for automobile door frame trims.

[0034] Example 2

[0035] (1) adding maleic acid, thioglycolic acid, and resin D301-R catalyst into a reactor filled with deionized water, wherein the mass ratio of maleic acid, thioglycolic acid, and resin D301-R catalyst is 1.3:1:0.04, stirring evenly, and reflux reaction at 95° C. for 6 hours. After the reaction is completed, the catalyst is filtered out while hot, and the deionized water is evaporated at 95° C., dried, and cooled to obtain carboxymethyl thiosuccinic acid;

[0036] (2) adding aminoethylaminopropyl silsesquioxane and acryloyl chloride to N,N-dimethylformamide solvent, stirring evenly, and then continuing to add triethylamine catalyst, wherein the mass ratio of aminoethylaminopropyl silsesquioxane, acryloyl chloride, and triethylamine catalyst is 1.5:1:0.02, reacting at 90° C. for 7 hours, and then performing reduced pressure distillation after the reaction, filtering and drying to obtain olefinated siloxane;

[0037] (3) adding divinyl glycol to N,N-dimethylformamide solvent, stirring and dispersing, and then adding allyl mercaptan and benzoin dimethyl ether photoinitiator, wherein the mass ratio of divinyl glycol, allyl mercaptan and benzoin dimethyl ether photoinitiator is 1:1.3:0.05, irradiating with 365 nm ultraviolet light at 45° C. for 5 h, centrifuging after the end, washing and drying to obtain intermediate 1;

[0038] (4) 16 parts by weight of phenolic resin and 13 parts by weight of epichlorohydrin were uniformly mixed, reacted at 80° C. for 12 hours, and then concentrated under reduced pressure and washed to obtain an epoxidized phenolic resin;

[0039] (5) adding 10 parts by weight of epoxidized phenolic resin and 16 parts by weight of acrylic acid to N,N-dimethylformamide solvent, stirring and mixing, reacting at 105° C. for 18 hours, and then distilling under reduced pressure, filtering, washing and drying to obtain an olefinated phenolic resin;

[0040] (6) adding 10 parts by weight of intermediate 1, 9 parts by weight of olefinic siloxane, 8 parts by weight of divinyl glycol, and 12 parts by weight of olefinic phenolic resin to N,N-dimethylformamide solvent for dissolution, adding 1 part by weight of azobisisobutyronitrile initiator after dissolution, reacting at 70° C. for 5 h, and removing the solvent by distillation under reduced pressure after the reaction, filtering, washing and drying to obtain intermediate 2;

[0041] (7) dissolving carboxymethyl thiosuccinic acid and intermediate 2 in a dimethyl sulfoxide solvent, then adding 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, wherein the mass ratio of carboxymethyl thiosuccinic acid, intermediate 2, 4-dimethylaminopyridine, and N,N-dicyclohexylcarbodiimide is 1:1.2:0.03:0.05, and reflux at 165° C. for 35 hours. After the reaction, cool and add methanol for precipitation, filter the solvent, and wash with distilled water, acetone, and ethanol in turn to obtain a silicon-containing hyperbranched polyester;

[0042] (8) 70 parts by weight of polyamide resin, 2 parts by weight of antioxidant H3386, and 8 parts by weight of silicon-containing hyperbranched polyester are added to a twin-screw extruder for melt blending, extrusion and granulation. The blending temperature is 245° C. and the extrusion temperature is 220° C.; and then the mixture is injection molded by an injection molding machine at an injection molding temperature of 240° C. to obtain an anti-oxidative and anti-aging polyamide material for automobile door frame trims.

[0043] Example 3

[0044] (1) adding maleic acid, thioglycolic acid, and resin D301-R catalyst into a reactor filled with deionized water, wherein the mass ratio of maleic acid, thioglycolic acid, and resin D301-R catalyst is 1.2:1:0.03, stirring evenly, and reflux reaction at 90° C. for 4.5 hours. After the reaction is completed, the catalyst is filtered out while hot, and the deionized water is evaporated at 87.5° C., dried, and cooled to obtain carboxymethyl thiosuccinic acid;

[0045] (2) adding aminoethylaminopropyl silsesquioxane and acryloyl chloride to N,N-dimethylformamide solvent, stirring evenly, and then continuing to add triethylamine catalyst, wherein the mass ratio of aminoethylaminopropyl silsesquioxane, acryloyl chloride, and triethylamine catalyst is 1.4:1:0.015, reacting at 85° C. for 5.5 hours, and then distilling under reduced pressure after the reaction, filtering and drying to obtain olefinated siloxane;

[0046] (3) adding divinyl glycol to N,N-dimethylformamide solvent, stirring and dispersing, and then adding allyl mercaptan and benzoin dimethyl ether photoinitiator, wherein the mass ratio of divinyl glycol, allyl mercaptan and benzoin dimethyl ether photoinitiator is 1:1.05:0.035, irradiating with 365 nm ultraviolet light at 32.5° C. for 4 h, centrifuging after irradiation, washing and drying to obtain intermediate 1;

[0047] (4) 13 parts by weight of phenolic resin and 10.5 parts by weight of epichlorohydrin were uniformly mixed, reacted at 75° C. for 9 hours, and then concentrated under reduced pressure and washed to obtain an epoxidized phenolic resin;

[0048] (5) adding 7.5 parts by weight of epoxidized phenolic resin and 13 parts by weight of acrylic acid to N,N-dimethylformamide solvent, stirring and mixing, reacting at 92.5° C. for 14 hours, and then distilling under reduced pressure, filtering, washing and drying to obtain an olefinated phenolic resin;

[0049] (6) adding 7.5 parts by weight of intermediate 1, 7.5 parts by weight of olefinic siloxane, 6 parts by weight of divinyl glycol, and 8.5 parts by weight of olefinic phenolic resin to N,N-dimethylformamide solvent for dissolution, adding 0.75 parts by weight of azobisisobutyronitrile initiator after dissolution, reacting at 65° C. for 3.5 hours, and removing the solvent by distillation under reduced pressure after the reaction, filtering, washing and drying to obtain intermediate 2;

[0050] (7) dissolving carboxymethyl thiosuccinic acid and intermediate 2 in a dimethyl sulfoxide solvent, then adding 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, wherein the mass ratio of carboxymethyl thiosuccinic acid, intermediate 2, 4-dimethylaminopyridine, and N,N-dicyclohexylcarbodiimide is 1:1.0:0.02:0.035, and reflux at 145° C. for 32.5 hours. After the reaction, cooling and adding methanol for precipitation, filtering the solvent, washing with distilled water, acetone, and ethanol in sequence, to obtain a silicon-containing hyperbranched polyester;

[0051] (8) 60 parts by weight of polyamide resin, 1.5 parts by weight of antioxidant H3386, and 6.5 parts by weight of silicon-containing hyperbranched polyester are added to a twin-screw extruder for melt blending, extrusion and granulation. The blending temperature is 227.5°C and the extrusion temperature is 215°C. The mixture is then injection molded by an injection molding machine at an injection molding temperature of 230°C to obtain an anti-oxidative and anti-aging polyamide material for automobile door frame trims.

[0052] Example 4

[0053] (1) adding maleic acid, thioglycolic acid, and resin D301-R catalyst into a reactor filled with deionized water, wherein the mass ratio of maleic acid, thioglycolic acid, and resin D301-R catalyst is 1.1:1:0.02, stirring evenly, and reflux reaction at 85° C. for 3 h. After the reaction is completed, the catalyst is filtered out while hot, and the deionized water is evaporated at 80° C., dried, and cooled to obtain carboxymethyl thiosuccinic acid;

[0054] (2) adding aminoethylaminopropyl silsesquioxane and acryloyl chloride to N,N-dimethylformamide solvent, stirring evenly, and then continuing to add triethylamine catalyst, wherein the mass ratio of aminoethylaminopropyl silsesquioxane, acryloyl chloride, and triethylamine catalyst is 1.3:1:0.01, reacting at 80° C. for 4 hours, and then distilling under reduced pressure after the reaction, filtering and drying to obtain olefinated siloxane;

[0055] (3) adding divinyl glycol to N,N-dimethylformamide solvent, stirring and dispersing, and then adding allyl mercaptan and benzoin dimethyl ether photoinitiator, wherein the mass ratio of divinyl glycol, allyl mercaptan and benzoin dimethyl ether photoinitiator is 1:1.3:0.05, irradiating with 365 nm ultraviolet light at 45° C. for 5 h, centrifuging after the end, washing and drying to obtain intermediate 1;

[0056] (4) 16 parts by weight of phenolic resin and 13 parts by weight of epichlorohydrin were uniformly mixed, reacted at 80° C. for 12 hours, and then concentrated under reduced pressure and washed to obtain an epoxidized phenolic resin;

[0057] (5) adding 7.5 parts by weight of epoxidized phenolic resin and 13 parts by weight of acrylic acid to N,N-dimethylformamide solvent, stirring and mixing, reacting at 92.5° C. for 14 hours, and then distilling under reduced pressure, filtering, washing and drying to obtain an olefinated phenolic resin;

[0058] (6) adding 7.5 parts by weight of intermediate 1, 7.5 parts by weight of olefinic siloxane, 6 parts by weight of divinyl glycol, and 8.5 parts by weight of olefinic phenolic resin to N,N-dimethylformamide solvent for dissolution, adding 0.75 parts by weight of azobisisobutyronitrile initiator after dissolution, reacting at 65° C. for 3.5 hours, and removing the solvent by distillation under reduced pressure after the reaction, filtering, washing and drying to obtain intermediate 2;

[0059] (7) dissolving carboxymethyl thiosuccinic acid and intermediate 2 in a dimethyl sulfoxide solvent, then adding 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, wherein the mass ratio of carboxymethyl thiosuccinic acid, intermediate 2, 4-dimethylaminopyridine, and N,N-dicyclohexylcarbodiimide is 1:1.0:0.02:0.035, and reflux at 145° C. for 32.5 hours. After the reaction, cooling and adding methanol for precipitation, filtering the solvent, washing with distilled water, acetone, and ethanol in sequence, to obtain a silicon-containing hyperbranched polyester;

[0060] (8) 60 parts by weight of polyamide resin, 1.5 parts by weight of antioxidant H3386, and 6.5 parts by weight of silicon-containing hyperbranched polyester are added to a twin-screw extruder for melt blending, extrusion and granulation. The blending temperature is 227.5°C and the extrusion temperature is 215°C. The mixture is then injection molded by an injection molding machine at an injection molding temperature of 230°C to obtain an anti-oxidative and anti-aging polyamide material for automobile door frame trims.

[0061] Example 5

[0062] (1) adding maleic acid, thioglycolic acid, and resin D301-R catalyst into a reactor filled with deionized water, wherein the mass ratio of maleic acid, thioglycolic acid, and resin D301-R catalyst is 1.3:1:0.04, stirring evenly, and reflux reaction at 95° C. for 6 hours. After the reaction is completed, the catalyst is filtered out while hot, and the deionized water is evaporated at 95° C., dried, and cooled to obtain carboxymethyl thiosuccinic acid;

[0063] (2) adding aminoethylaminopropyl silsesquioxane and acryloyl chloride to N,N-dimethylformamide solvent, stirring evenly, and then continuing to add triethylamine catalyst, wherein the mass ratio of aminoethylaminopropyl silsesquioxane, acryloyl chloride, and triethylamine catalyst is 1.5:1:0.02, reacting at 90° C. for 7 hours, and then performing reduced pressure distillation after the reaction, filtering and drying to obtain olefinated siloxane;

[0064] (3) adding divinyl glycol to N,N-dimethylformamide solvent, stirring and dispersing, and then adding allyl mercaptan and benzoin dimethyl ether photoinitiator, wherein the mass ratio of divinyl glycol, allyl mercaptan and benzoin dimethyl ether photoinitiator is 1:1.3:0.05, irradiating with 365 nm ultraviolet light at 45° C. for 5 h, centrifuging after the end, washing and drying to obtain intermediate 1;

[0065] (4) 16 parts by weight of phenolic resin and 13 parts by weight of epichlorohydrin were uniformly mixed, reacted at 80° C. for 12 hours, and then concentrated under reduced pressure and washed to obtain an epoxidized phenolic resin;

[0066] (5) adding 7.5 parts by weight of epoxidized phenolic resin and 13 parts by weight of acrylic acid to N,N-dimethylformamide solvent, stirring and mixing, reacting at 92.5° C. for 14 hours, and then distilling under reduced pressure, filtering, washing and drying to obtain an olefinated phenolic resin;

[0067] (6) adding 7.5 parts by weight of intermediate 1, 7.5 parts by weight of olefinic siloxane, 6 parts by weight of divinyl glycol, and 8.5 parts by weight of olefinic phenolic resin to N,N-dimethylformamide solvent for dissolution, adding 0.75 parts by weight of azobisisobutyronitrile initiator after dissolution, reacting at 65° C. for 3.5 hours, and removing the solvent by distillation under reduced pressure after the reaction, filtering, washing and drying to obtain intermediate 2;

[0068] (7) dissolving carboxymethyl thiosuccinic acid and intermediate 2 in a dimethyl sulfoxide solvent, then adding 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, wherein the mass ratio of carboxymethyl thiosuccinic acid, intermediate 2, 4-dimethylaminopyridine, and N,N-dicyclohexylcarbodiimide is 1:0.8:0.01:0.02, and reflux at 125° C. for 30 hours. After the reaction, cool and add methanol for precipitation, filter the solvent, and wash with distilled water, acetone, and ethanol in turn to obtain a silicon-containing hyperbranched polyester;

[0069] (8) 50 parts by weight of polyamide resin, 1 part by weight of antioxidant H3386, and 5 parts by weight of silicon-containing hyperbranched polyester are added to a twin-screw extruder for melt blending, extrusion and granulation. The blending temperature is 210° C. and the extrusion temperature is 210° C.; then, the mixture is injection molded by an injection molding machine at an injection molding temperature of 220° C. to obtain an anti-oxidative and anti-aging polyamide material for automobile door frame trims.

[0070] Comparative Example 1

[0071] (1) 50 parts by weight of polyamide resin and 1 part by weight of antioxidant H3386 are added to a twin-screw extruder for melt blending, extrusion and granulation, the blending temperature is 210° C., and the extrusion temperature is 210° C.; then, the mixture is injection molded by an injection molding machine, and the injection molding temperature is 220° C. to obtain an anti-oxidation and aging polyamide material for automobile door frame trims.

[0072] Performance Test:

[0073] Oxygen index (LOI) test The flame retardancy of the sample is tested using a digital oxygen index meter.

[0074] Vertical burning test (UL-94) uses CZF-2 vertical burning test instrument to test the samples. The test standard is based on ASTM D380. TPU sample size: 120×120×2mm 3 .

[0075] Table 1: Flame retardancy tests.

[0076] project Oxygen index (%) Vertical combustion Example 1 45.3 V-0 Example 2 48.1 V-0 Example 3 47.6 V-0 Example 4 47.3 V-0 Example 5 47.8 V-0 Comparative Example 1 35.2 V-1

[0077] It can be seen from Table 1 that the anti-oxidation and aging polyamide material for automobile door frame trims prepared in the present invention, Examples 1-5 have better flame retardant effects than Comparative Example 1.

[0078] The mechanical properties of the materials were tested using a universal tensile tester.

[0079] Table 2: Tensile strength test.

[0080]

[0081]

[0082] It can be seen from Table 2 that Examples 1-5 of the present invention have better stretching effects than Comparative Example 1.

[0083] The materials prepared above were prepared into vehicle test specimens by injection molding and subjected to long-term heat aging (test temperature 140±2°C, aging time 1000±5h). Yellowing resistance: the material to be tested was injection molded into a 70mm×70mm×1mm sheet, placed in an aging experiment oven with internal circulation at 80°C, and the yellowness index (YI value) of the sheet was tested every 24h. The specific test steps were carried out in accordance with the contents described in HG / T 3862-2006, and the test instrument was an American X-Rite colorimeter.

[0084] Table 3: Anti-aging and antioxidant tests.

[0085]

[0086]

[0087] It can be seen from Table 3 that Examples 1-5 of the present invention have better anti-aging and anti-oxidation effects than Comparative Example 1.

[0088] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0089] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An anti-oxidation and aging polyamide material for automobile door frame trim, characterized in that: The invention comprises the following components by weight: 50-70 parts by weight of polyamide resin, 1-2 parts by weight of antioxidant H3386, and 5-8 parts by weight of silicon-containing hyperbranched polyester; The preparation method of the silicon-containing hyperbranched polyester comprises the following steps: (1) adding maleic acid, thioglycolic acid and resin D301-R catalyst into a reactor filled with deionized water, stirring evenly, and reflux reacting at 85-95° C. for 3-6 hours. After the reaction is completed, filtering out the catalyst while hot, evaporating the deionized water at 80-95° C., drying and cooling to obtain carboxymethyl thiosuccinic acid; (2) adding aminoethylaminopropylsilsesquioxane and acryloyl chloride to N,N-dimethylformamide solvent, stirring evenly, and then adding triethylamine catalyst thereto, reacting at 80-90° C. for 4-7 hours, and then performing reduced pressure distillation after the reaction, filtering and drying to obtain olefinated siloxane; (3) adding divinyl glycol to N,N-dimethylformamide solvent, stirring and dispersing, then adding allyl mercaptan and benzoin dimethyl ether photoinitiator, irradiating with 365 nm ultraviolet light at 20-45° C. for 3-5 h, centrifuging, washing and drying to obtain intermediate 1; (4) adding 5-10 parts by weight of intermediate 1, 6-9 parts by weight of olefinic siloxane, 4-8 parts by weight of divinyl glycol, and 5-12 parts by weight of olefinic phenolic resin to N,N-dimethylformamide solvent for dissolution, adding 0.5-1 parts by weight of azobisisobutyronitrile initiator after dissolution, reacting at 60-70° C. for 2-5 hours, removing the solvent by distillation under reduced pressure after the reaction, filtering, washing and drying to obtain intermediate 2; (5) dissolving carboxymethyl thiosuccinic acid and intermediate 2 in dimethyl sulfoxide solvent, then adding 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, and reflux at 125-165° C. for 30-35 hours. After the reaction, cooling and adding methanol for precipitation, filtering the solvent, and washing with distilled water, acetone, and ethanol in sequence to obtain a silicon-containing hyperbranched polyester; The mass ratio of maleic acid, thioglycolic acid and resin D301-R catalyst in (1) is 1.1-1.3:1:0.02-0.04; The mass ratio of aminoethylaminopropylsilsesquioxane, acryloyl chloride and triethylamine catalyst in (2) is 1.3-1.5:1:0.01-0.02; The mass ratio of divinyl glycol, allyl mercaptan and benzoin dimethyl ether photoinitiator in (3) is 1:0.8-1.3:0.02-0.05; The preparation method of the olefinic phenolic resin in (4) is as follows: S1. 10-16 parts by weight of a phenolic resin and 8-13 parts by weight of epichlorohydrin are mixed uniformly, reacted at 70-80 ° C for 6-12h, and then concentrated under reduced pressure and washed to obtain an epoxidized phenolic resin; S2. Add 5-10 parts by weight of an epoxidized phenolic resin and 10-16 parts by weight of acrylic acid to an N,N-dimethylformamide solvent, stir and mix, react at 80-105 ° C for 10-18h, and then distill under reduced pressure, filter, wash and dry to obtain an olefinic phenolic resin; The mass ratio of carboxymethylthiosuccinic acid, intermediate 2,4-dimethylaminopyridine, and N,N-dicyclohexylcarbodiimide in (5) is 1:0.8-1.2:0.01-0.03:0.02-0.05; The preparation method of the anti-oxidation and aging polyamide material for automobile door frame trim strips comprises: adding polyamide resin, antioxidant H3386 and silicon-containing hyperbranched polyester into a twin-screw extruder for melt blending, extrusion and granulation, the blending temperature is 210-245° C., and the extrusion temperature is 210-220° C.; and then injection molding by an injection molding machine, the injection molding temperature is 220-240° C., so as to obtain the anti-oxidation and aging polyamide material for automobile door frame trim strips.

Citation Information

Patent Citations

  • Organic-inorganic composite heat conductive filler as well as preparation method and application thereof

    CN104672495A

  • Preparation method of high-performance modified polyethersulfone resin

    CN105331081A